Pore-scale investigation of phase change heat storage enhancement in gradient finned metal foams - Huo, Guanping; Guo, Xueyan; Zhao, Wei; Zhang, Jian; Rong, Wanting (Applied thermal engineering, 2025)
•Pore-scale simulation reveals thermal behaviour of paraffin in finned metal foam structures.•Finned metal foams outperform single-fin or foam in latent heat storage enhancement.•Positive porosity gradient reduces PCM melting time by 14.2% over negative gradient.•Copper skeletons yield up to 43.8% shorter phase change duration than aluminum. This study presents a detailed pore-scale numerical investigation of the melting behaviour of phase change materials embedded in gradient finned metal foams using a structure-resolved computational fluid dynamics approach. An idealised geometric model was developed based on the Kelvin cell units, thereby enabling precise control over porosity gradients by varying skeleton dimensions along the heat flow direction. The findings demonstrate that the incorporation of longitudinal fins into the metal foam significantly enhances heat conduction and accelerates phase change materials melting. The configuration exhibiting a positive porosity gradient demonstrated optimal performance, exhibiting a 14.2% reduction in total melting time than that for a negative gradient configuration. Furthermore, the replacement of aluminium with copper as the skeleton material resulted in a 43.9% reduction in melting duration, thereby demonstrating the critical influence of thermal conductivity. The study presents novel insights into the design of composite finned metal foam structures and highlights effective strategies for improving the efficiency of latent heat energy storage systems.